La figure de l’Abandonné·e. La littérature médiévale comme manuel d’un retour à soi ? - Dominique Demartini (Perspectives Médiévales)
This study aims to reinvestigate the scenarios of the Abandoned within the dialectic of power relations and submission, losses and gains. To circulate these notions, it will rely on those of situated knowledge and standpoint (Donna Haraway, Sandra Harding). Embracing an androcentric viewpoint, it will attempt to illuminate the masculine presuppositions and the contribution of texts to the construction of a heroine figure, paradoxically become exemplary. To these masculine constructions, it will oppose their reappropriations as plural feminine experiences through which, between submission and suicide, the abandoned women experience more subtle modes of agency and repair. If medieval fictions are also not lacking in abandoned lovers, do they not also draw, between self-destruction or that of the other, the paths of a return to oneself, and why not, models of resilience for today's men in the face of the ordeal of abandonment?